Research Brief One-Sheet No.8: The Impact of Police Crime on LGBTQ+ People - Stinson, Philip M (2016)
This research brief provides a summary of a research presentation at the Forum on 21st Century Policing: Protecting the Rights of LGBTQ+ People held by the Office of Community Oriented Policing Services at the U.S. Department of Justice, on July 21, 2016, in Washington, DC